Mid-upper arm circumference in pregnant women and its relation to birth weight - Ricalde, Anamaría E.; Velásquez-Meléndez, Gustavo; Tanaka, Ana Cristina d'A.; Siqueira, Arnaldo A.F. de (Revista de Saúde Pública, 1998)
OBJECTIVE: In order to determine the relationship between some maternal anthropometric indicators and birth weight, crown-heel length and newborn's head circumference, 92 pregnant women were followed through at the prenatal service of hospital in S. Paulo, Brazil. MATERIAL AND METHOD: The following variables were established for the mother: weight, height, mid-upper arm circumference, pre-pregnancy weight, gestational weight gain and Quetelet's index. For the newborn the following variables were recorded: birth weight, crown-heel length, head circumference and gestational age by Dubowitz's method. RESULTS: Significant associations were noted between gestational age and newborn variables. In addition, maternal mid-arm circumference (MUAC) and pre-pregnancy weight were found to be positively correlated to birth weight (r=0.399; r=0.378, respectively). The multivariate linear regression shows that gestational age, mother's arm circumference and pre-pregnancy weight continue to be significant predictors of birth weight. On the other hand, only gestational age and mother's age was associated with crown-heel length. Similarly MUAC was significantly associated with crown-heel length (r= 0.306; P=0.0030). CONCLUSION: Maternal mid-upper arm circumference is a potential indicator of maternal nutritional status. It could be used in association with other anthropometric measurements, instead of pre-pregnancy weight, as an alternative indicator to assess women at risk of poor pregnancy outcome.